Striking beauty : a philosophical look at the Asian martial arts - Allen, Barry, 1957- (Columbia University Press, 2015)
"The first book to focus on the intersection of Western philosophy and the Asian martial arts, Striking Beauty comparatively studies the historical and philosophical traditions of martial arts practice and their ethical value in the modern world. Expanding Western philosophy's global outlook, the book forces a theoretical reckoning with the concerns of Chinese philosophy and the aesthetic and technical dimensions of martial arts practice. Striking Beauty explains the relationship between Asian martial arts and the Chinese philosophical traditions of Confucianism, Buddhism, and Daoism, in addition to Sunzi's Art of War. It connects martial arts practice to the Western concepts of mind-body dualism and materialism, sports aesthetics, and the ethics of violence. The work ameliorates Western philosophy's hostility toward the body, emphasizing the pleasure of watching and engaging in martial arts, along with their beauty and the ethical problem of their violence."--Publisher's description